Pengaruh Penerapan Model AIDA terhadap Minat Konsumen dalam Kampanye Digital Skintific di Instagram - Dwi Marta Chintya; Ika Nur Fatihah; Nur Zulfatul Laila; Waris Adi Darmawan; M. Miftahur Rohmat (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to examine the influence of the AIDA model (Attention, Interest, Desire, Action) on consumer interest in Skintific’s digital campaign on Instagram. This research employs a descriptive quantitative approach. Data were collected through an online questionnaire distributed to 22 respondents who are Instagram users and aware of Skintific's digital campaign. The research instrument consisted of 20 statement items based on the indicators of the AIDA model and consumer interest, using a 5-point Likert scale. The data analysis technique used was descriptive analysis by calculating the average score of each AIDA dimension and consumer interest. The results show that the Interest and Desire dimensions obtained the highest average scores, indicating a strong consumer attraction and desire toward the product. Meanwhile, the Action and Consumer Interest dimensions showed moderate scores, suggesting the need for enhanced campaign strategies to drive real consumer action. This study contributes theoretically by confirming the relevance of the AIDA model in the context of digital marketing and offers practical implications for skincare brands to optimize their campaign strategies on social media platforms.